(untitled) (Research, Society and Development, 2020)
The role of male teachers in the first stage of education is recent in Brazil, but the gradual increase in the male presence has demystified the assumption that teaching is a space exclusively for women. And in Paraguay, how do male teachers work with young children? The present study aimed to investigate the opinion of the school community, understood as teachers, family members and managers, of pre-school education in Salto Del Guairá PY, in relation to the educational work developed by male teachers with children. The field research was carried out through the recording of interviews, guided by a semi-structured script, with a total of five people, being: two male teachers, two school administrators and a father of a girl who studied with a male teacher in pre-school education. Paraguayan school system. All participants spoke the Spanish language, but the data were transcribed in Portuguese and subsequently analyzed. The results show that there is an understanding that men can educate children, but care must be assumed by women. And just as in Brazil, also in Salto Del Guairá PY the idea that students respect male teachers is more prevalent, because they impose greater discipline in the classroom.